2008
DOI: 10.1007/s11274-008-9913-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of diosgenin and its precursor furostanol glycosides

Abstract: Microorganisms have been screened for biotransformational activity against diosgenin or its precursor furostanol glycosides obtained from fenugreek seed (Trigonella foenum-graecum). Using diosgenin as the substrate, Cunninghamella elegans and Aspergillus nidulans produced some androstenes when a,a 0 -dipyridyl was supplemented to the transformation medium. Also, using the glycosides as a substrate, Rhizopus sp. produced diosgenin in [90% yield from the glycoside. The parameters were optimized to increase the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…At low concentration of agar-agar, very fragile gel beads are formed that also results in less enzyme entrapment within their micro-environment and unfortunately, due to the large pore size; the likelihood of enzyme leakage also increases during repeated washing of the beads. Molecular structure of an enzyme also affects the immobilization yield and it was reported that 4.0% agar-agar concentration was optimum for achieving maximum immobilization yield for amylase [13] and lipase [16]. However, for the entrapment of pectinase, 80.0% yield was achieved with 3.0% concentration of agar-agar [12].…”
Section: Agar-agar Concentrationmentioning
confidence: 99%
“…At low concentration of agar-agar, very fragile gel beads are formed that also results in less enzyme entrapment within their micro-environment and unfortunately, due to the large pore size; the likelihood of enzyme leakage also increases during repeated washing of the beads. Molecular structure of an enzyme also affects the immobilization yield and it was reported that 4.0% agar-agar concentration was optimum for achieving maximum immobilization yield for amylase [13] and lipase [16]. However, for the entrapment of pectinase, 80.0% yield was achieved with 3.0% concentration of agar-agar [12].…”
Section: Agar-agar Concentrationmentioning
confidence: 99%
“…Curvularia lunata, Penicillium melinii, Aspergillus niger and Rhizopus sp. have been identified to selectively cleave the glycosyl residue of steroidal saponins at C-3 (Feng et al 2005;He et al 2006a;He et al 2006b;Adham et al 2009). More recently, an eco-friendly process with multi-enzymes (including commercial cellulase, amylase, glucoamylase, b-glucosidase, and pectinase) for hydrolysis is used to produce diosgenin from the raw material .…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of carbon sources by D. zingiberensis directly affects the growth of strains, which is considered as a prerequisite for biotransformation. Enzymes secreted as part of the metabolism of probiotic Lactobacillus strains could effectively convert saponin to diosgenin and are hence considered as the tool for biotransformation [20]. Lactic acid secreted during fermentation will restrict the growth and biotransformation.…”
Section: Introductionmentioning
confidence: 99%